Comparing Ecosystem Service Preferences between Urban and Rural Dwellers. (16th January 2019) - Lapointe, Marie; Cumming, Graeme S; Gurney, Georgina G
Abstract: Urbanization can profoundly alter socioecological relationships, but its influence on how people perceive and value ecosystem services (ES) is poorly understood. We reviewed an emerging literature in which sociocultural valuation of ES is compared among urban and rural dwellers. This research suggests that, although regulating and cultural ES were highly valued by both rural and urban dwellers, urban dwellers tended to value provisioning ES less than rural dwellers did. Differences in ES valuation could result from different experiences, uses, and needs for ES of urban and rural dwellers. We also identified two key gaps in the literature that relate to understanding how diverse ES contribute differently to the well-being of rural and urban populations (and the relevance of these differences for environmental education and policy) and the changing roles of ES in developing countries and vulnerable ecosystems, such as small islands, that face pressing environmental, social, and economic challenges.